Effects of porosity on the fatigue life of polyamide 12 considering crack initiation and propagation. (3rd July 2020) - Kim, Youn Jun; You, Hangil; Kim, Sung Jun; Yun, Gun Jin
Abstract : Internal pores in composite materials generated during fabrication processing can induce negative influences on the physical properties. Among them, the fatigue life under repetitive loadings is one of the most detrimentally influenced properties by the undesirable pores. In this paper, we investigated the effect of pore geometries – 1) sizes and 2) aspect ratios on the fatigue life of polyamide 12 (PA12) by combining two different fatigue life prediction approaches. Considering that the typical failure mechanism of structural materials follows the initiation of the crack, propagation, and ultimate separation, the present approach counts the fatigue life until crack initiation and fatigue cycles during the crack growth until complete separation. For the prediction, a crack growth model by Castillo-Canteli-Siegele model (CCS model) with initial defects was adopted. In addition, to reflect the elastoplastic behavior better, an extended CCS model with the cyclic J-integral was used. The simulation results show that the presence of the pores in the plastic material can significantly affect the fatigue life. The characteristics of fatigue properties on the geometric conditions of pores were discussed by comparing the results. The proposed method can be seamlessly used for the evaluation of fatigue life of polymer matrix composite materials.